IDENTIFIKASI DAN KONSERVASI NASKAH LONTAR KOLEKSI GRIYA PEMEREGAN DENPASAR - Erawati, N.K. Ratna; Sulibra, I K N.; Widana, I B G. (Buletin Udayana Mengabdi, 2012)
Cultural heritage recorded on palm leaves manuscripts in Bali, especially in Sub-District Pemeregan Griya Pemecutan Denpasar City is a priceless legacy. It is necessary for the preservation of manuscripts through conservation activities and identify both physical and contents. Based on the results of activities conducted in 98 manuscripts palmyra fruit. 98 pieces of text are identified as many as 92 fruits and fruit 6 are unidentified or damaged. The identified scripts can be classified into 38 types of fruit Vedas; religion as much as 4 pieces; tutur as many as 43 pieces; itihasa as many as 4 pieces; babad of 2 pieces; tantri one, and as many as 6 palmyra fruit are damaged. Identification was obtained after all the palmyra manuscripts were conserved and they can be clearly read.